M2 tumor‑associated macrophages promote tumor progression in non‑small‑cell lung cancer - Sumitomo, Ryota; Hirai, Tatsuya; Fujita, Masaaki; Murakami, Hiroaki; Otake, Yosuke; Huang, Cheng‑Long (Experimental and therapeutic medicine, 2019)
Tumor-associated macrophages (TAMs) are key components of the tumor microenvironment that can be polarized into different phenotypes, including tumor-inhibiting M1 macrophages and tumor-promoting M2 macrophages. To elucidate the biological and clinical significance of M2 TAMs in non-small-cell lung cancer (NSCLC), a comprehensive clinical assessment of the tissue distribution of M2 TAMs was performed. The tissue distribution of M2 TAMs was retrospectively analyzed using CD163 immunohistochemistry in 160 consecutive patients who underwent NSCLC resection. Tumor proliferation was evaluated via the Ki-67 proliferation index. The results revealed that the stromal density of M2 TAMs was significantly associated with the C-reactive protein (CRP) level (P=0.0250), the Ki-67 proliferation index (P=0.0090) and invasive size (P=0.0285). Furthermore, the stromal M2 TAM density was significantly associated with tumor differentiation (P=0.0018), lymph node metastasis (P=0.0347) and pathological stage (P=0.0412). The alveolar M2 TAM density was also significantly associated with the CRP level (P=0.0309), invasive size (P<0.0001), tumor differentiation (P=0.0192), tumor status (P=0.0108) and pathological stage (P=0.0110). By contrast, no association was observed between islet M2 TAM density and the aforementioned biological and clinical factors. In regards to prognosis, disease-free survival rate was significantly lower in patients with stromal M2 TAM-high tumors (P=0.0270) and in those with alveolar M2 TAM-high tumors (P=0.0283). Furthermore, the overall survival rate was also significantly lower in patients with stromal M2 TAM-high tumors (P=0.0162) and in those with alveolar M2 TAM-high tumors (P=0.0225). Therefore, during NSCLC progression, M2 TAMs may induce tumor cell aggressiveness and proliferation and increase metastatic potential, resulting in a poor prognosis in patients with NSCLC.